2020
DOI: 10.1038/s41598-020-70159-y
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent platform for ultrasound diagnosis of thyroid nodules

Abstract: This paper proposed a non-segmentation radiological method for classification of benign and malignant thyroid tumors using B mode ultrasound data. This method aimed to combine the advantages of morphological information provided by ultrasound and convolutional neural networks in automatic feature extraction and accurate classification. Compared with the traditional feature extraction method, this method directly extracted features from the data set without the need for segmentation and manual operations. 861 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…All the evaluated studies showed significant high overall diagnostic accuracy of CNNs, above 90%, which does not differ much from that of expert radiologists. In particular, most of the studies demonstrate a comparable diagnostic accuracy, such as Watkins et al, Bai et al, Ye et al, Koh et al, and Fresilli et al [ 4 , 16 , 20 , 30 , 40 ]. Approximately the same number of studies demonstrate a higher diagnostic accuracy of AI systems compared to that of expert radiologists (e.g., Sun et al, Peng et al, and Zhou et al) [ 15 , 22 , 23 ], or vice versa, a superiority of diagnostic accuracy by expert radiologists compared to that of AI systems (e.g., Zhang et al and Han et al) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the evaluated studies showed significant high overall diagnostic accuracy of CNNs, above 90%, which does not differ much from that of expert radiologists. In particular, most of the studies demonstrate a comparable diagnostic accuracy, such as Watkins et al, Bai et al, Ye et al, Koh et al, and Fresilli et al [ 4 , 16 , 20 , 30 , 40 ]. Approximately the same number of studies demonstrate a higher diagnostic accuracy of AI systems compared to that of expert radiologists (e.g., Sun et al, Peng et al, and Zhou et al) [ 15 , 22 , 23 ], or vice versa, a superiority of diagnostic accuracy by expert radiologists compared to that of AI systems (e.g., Zhang et al and Han et al) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 166 studies from January 2012 to April 2022; of these, 63 were further considered. After a full text read, the final studies included in the review were 30 in number; they are all listed below in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lack of universal scanning sequence patterns supports the somewhat opportunistic nature of anomaly scanning. Unlike non-obstetric ultrasound, obstetric ultrasound scans are restricted by fetal position and movement 22,23 . It is likely that while performing anomaly scans, sonographers have a preferred scanning sequence, and at the same time, take advantage of the fetal position, capturing structures that are more favorably visualized in each part of the scan.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, application of artificial intelligence technology in the medicine has gradually increased, especially in imaging [3][4][5] and signal [6]. How to use information of ultrasound images to establish a computerassisted automated thyroid diagnosis system is an important direction of current research [7,8].…”
Section: Introductionmentioning
confidence: 99%